Utilization of Dimethyl Sulfide as a Sulfur Source with the Aid of Light by Marinobacterium sp. Strain DMS-S1 - Fuse, Hiroyuki (American Society for Microbiology, 2000)
Strain DMS-S1 isolated from seawater was able to utilize dimethyl sulfide (DMS) as a sulfur source only in the presence of light in a sulfur-lacking medium. Phylogenetic analysis based on 16S ribosomal DNA genes indicated that the strain was closely related to Marinobacterium georgiense. The strain produced dimethyl sulfoxide (DMSO), which was a main metabolite, and small amounts of formate and formaldehyde when grown on DMS as the sole sulfur source. The cells of the strain grown with succinate as a carbon source were able to use methyl mercaptan or methanesulfonate besides DMS but not DMSO or dimethyl sulfone as a sole sulfur source. DMS was transformed to DMSO primarily at wavelengths between 380 and 480 nm by heat-stable photosensitizers released by the strain. DMS was also degraded to formaldehyde in the presence of light by unidentified heat-stable factors released by the strain, and it appeared that strain DMS-S1 used the degradation products, which should be sulfite, sulfate, or methanesulfonate, as sulfur sources.